Mechanical property characterisation of napier grass fibre reinforced polyester composites - Muhammad Haameem Jameel Ahamed (School of Mechatronic Engineering, 2016)
The scope in this investigation is to extract Napier grass fibre using water retting process. Then it is extended to treat the fibres with NaOH at four different concentrations (5, 10, 15 and 20%). Fabrication of the Napier grass fibre reinforced composites by using unsaturated polyester resin at 10%, 15%, 20%, 25% and 30% volume fractions of fibre is needed to carry out. The composite laminates will then be subjected to tensile and flexure tests to determine the mechanical properties in accordance to the standard ASTM D638 and ASTM D790 respectively. Results obtained will be analyzed and characterized to evaluate the tensile and flexural properties of Napier grass fibre reinforced composites. Further investigation on the effects of moisture and thermal will be incorporated into this investigation. Results of the characterization of Napier grass fibre are to be compared with the mechanical properties of more traditionally available natural fibres.